OPTIMALISASI DIGITAL BAGI ONLINE SHOP YOURFIRSTSTEP.ID - Jacelyn Yeo (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
All businesses have a responsibility to promote their products or services using various channels in order to maximize profitability. Digital marketing necessitates the presence of distinctive and well-prepared promotional efforts to effectively attain business objectives. Social media marketing is a commonly employed approach by micro, small, and medium enterprises (MSMEs). The level of customer brand awareness can significantly impact their purchasing decisions. It is important for a brand to have a clear and consistent personality that aligns with the brand's values ​​and target audience. The objective of this research is to investigate the marketing strategies being implemented by these MSMEs and assess customer brand awareness. A qualitative research methodology was employed for this study, and the findings highlight the significant influence of marketing communication within a company on brand awareness.